Impact of Internet Addiction on Workplace Procrastination: An Empirical Study on Millennial Employees - Kastiya, Shweta; Sharma, Arti (Prabandhan: Indian Journal of Management, 2020)
This paper examined the factors of Internet addiction and workplace procrastination among millennial employees. The research design of the empirical study was descriptive and the impact of 20 factors, each of Internet addiction and workplace procrastination, were studied on millennial employees. The study was conducted on a sample of 103 millennial employees. The selected factors of Internet addiction were reduced to two and selected factors affecting workplace procrastination were reduced to three dimensions, respectively using exploratory factor analysis (EFA). Pearson’s correlation and regression analysis were used for testing the research hypotheses The respondents of the study were millennial employees from different corporate sectors. Internet addiction for social media was found to be positively related to anxious workplace procrastination among millennial employees, which means that the respondents who spent more time on various social media platforms were more inclined towards a delay in their tasks due to high level of anxiety. The study has important implications for millennial employees and their employers and presented an elementary framework to strategically develop the plans in order to reduce the addiction of the Internet so that employees’ performance can be improved at the workplace.